2017
DOI: 10.1038/cddis.2017.177
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PTP1B disrupts cell–cell adhesion and induces anoikis in breast epithelial cells

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a well-known inhibitor of insulin signaling pathways and inhibitors against PTP1B are being developed as promising drug candidates for treatment of obesity. PTP1B has also been linked to breast cancer both as a tumor suppressor and as an oncogene. Furthermore, PTP1B has been shown to be a regulator of cell adhesion and migration in normal and cancer cells. In this study, we analyzed the PTP1B expression in normal breast tissue, primary breast cells and the breast epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…We applied GISTIC algorithm (36) to perform focal CNA analysis and identified a number of candidate genes, including driver genes from other tumor types, as well as genes not previously reported to be associated with any cancer. Over-expression of PTPN1 has been linked to colon cancer and breast cancer development and progression (54,55). The phosphatase activity of PTPN1 is responsible for the regulation of cell motility and invasion, and may enhance the expression of EGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied GISTIC algorithm (36) to perform focal CNA analysis and identified a number of candidate genes, including driver genes from other tumor types, as well as genes not previously reported to be associated with any cancer. Over-expression of PTPN1 has been linked to colon cancer and breast cancer development and progression (54,55). The phosphatase activity of PTPN1 is responsible for the regulation of cell motility and invasion, and may enhance the expression of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…It directly dephosphorylates insulin receptor and insulin receptor substrates, which results in down regulation of insulin signaling. In recent studies, the overexpression of PTPN1 was detected in several cancer types such as colon cancer and breast cancer (54,55). It has also been reported as an indicator of poor prognosis in gastric cancer (56).…”
Section: Driver Gene Identificationmentioning
confidence: 98%
“…Work form several groups has demonstrated that protein tyrosine phosphatases play a relevant role in the process of macrophage polarization acting, not only as negative regulators of pro-inflammatory signaling, but also as attenuators of anti-inflammatory pathways [21] , [33] , [34] , [35] , [36] , [37] . Moreover, in addition to immune regulation, an essential role for PTP1B in obesity-induced chronic low-grade inflammation and in other pathologies including diabetes, cancer, neuroinflammation, liver diseases or Rett syndrome, has been described as evidenced by the use of selective PTP1B inhibitors or animal models targeted for PTP1B [12] , [18] , [20] , [22] , [38] , [39] , [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PTP1B in breast cancer cells leads to cell death and loss of extracellular matrix fixation, leading to negative regulation of cell adhesion proteins and interrupted actin polymerization. They saw that with the inhibition of PTP1B the activity of Src is consequently decreased by the adhesion pathway and motility is impaired [78].…”
Section: Ptps Contribute For Metastasis Through Extracellular Matrix mentioning
confidence: 99%